Áp dụng định lý pitago cho hai tam giác vuông HAB và HAD, ta có:
$$\begin{cases}
AB^2 = AH^2 + BH^2 & \\
AD^2 = AH^2 + HD^2 & \\
\end{cases} $$
\Rightarrow$ AB^2 - AD^2 = BH^2 - HD^2$(*)
Áp dụng định lý pitago cho tam giác vuông HBC và HCD, ta có :
$$\begin{cases}
BC^2 = HB^2 + HC^2 & \\
CD^2 = HD^2 + HC^2 & \\
\end{cases} $$
\Rightarrow $BC^2 - CD^2 = HB^2 - HD^2$ %%-
Từ (*) và %%- ,suy ra :
$AB^2 - AD^2 - (BC^2 - CD^2) = 0$
\Leftrightarrow $AB^2 - AD^2 - BC^2 + CD^2 = 0$
\Leftrightarrow $AB^2 + CD^2 = BC^2 + AD^2$\Rightarrow ĐPCM